Is Emission Intensity or Output U-shaped in the Strictness of Environmental Policy - Bouwe Dijkstra; Maria J. Gil-Moltó (Center for Economic Studies and ifo Institute (CESifo), 2014)
In a model where firms face a continuous choice of how much to invest in environmental innovation, we show that an ever stricter environmental policy does not always lead to ever cleaner production methods and ever lower production of polluting goods. It does so when the abatement technology is end-of-pipe. When the abatement technology is integrated however, either emission intensity or output is U-shaped in the strictness of policy. If the emission intensity is U-shaped, it will reach its lowest value at the point where the Marginal Abatement Cost curves intersect. These results hold with emission taxation (whether firms are price-takers or they interact strategically on the output market) as well as in the social optimum.
Keywords: L13; Q55; Q58; 330; environmental innovation; environmental taxation; oligopoly; marginal abatement costs